2020
DOI: 10.3892/etm.2020.8542
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cytogenetic characterization of small supernumerary marker 15 in infertile male: A case report

Abstract: Small supernumerary marker chromosomes (sSMCs) are defined as structurally abnormal chromosomes that may be detected pre-or postnataly in patients with developmental and/or mental retardation or infertility. sSMC on chromosome 15 accounts for the highest proportion of all sSMCs and may be detected in subfertile individuals. The present study reports the case of a male patient with oligoasthenoteratozoospermia and an sSMC. The sSMC was identified and characterized according to G-banding analysis, chromosomal mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…Armanet et al [2015] found that 72% of sSMCs detected in association with infertility are derived from acrocentric chromosomes [Armanet et al, 2015]. Some hypotheses have been advanced to explain the cause of infertility in these men, such as the presence of an interchromosomal effect [Guediche et al, 2012;Armanet et al, 2015] and/or an association between the NOR and meiotic abnormalities [Sun et al, 2020].…”
Section: Discussionmentioning
confidence: 99%
“…Armanet et al [2015] found that 72% of sSMCs detected in association with infertility are derived from acrocentric chromosomes [Armanet et al, 2015]. Some hypotheses have been advanced to explain the cause of infertility in these men, such as the presence of an interchromosomal effect [Guediche et al, 2012;Armanet et al, 2015] and/or an association between the NOR and meiotic abnormalities [Sun et al, 2020].…”
Section: Discussionmentioning
confidence: 99%
“…Catsper is also located in this area of the genome and defects in this critical sperm component are also associated with male infertility (210). The presence of small supernumerary marker chromosomes (sSMCs) is similarly associated with severe male infertility involving oligoasthenoteratozoospermia and most commonly involves chromosome 15 (211). Large deletions on chromosome 15 including the Catsper gene, and another gene also associated with spermatozoa, STRC (stereocilin), have also been linked to a rare condition characterized by male infertility and deafness (212).…”
Section: A Unifying Concept: Oxidative Dna Damage Infertility and Ofmentioning
confidence: 99%